Cysts of Follicular Origin, Not Always Benign and in the Scalp; [Quistes de Origen Folicular, No Siempre Benignos Ni en el Cuero Cabelludo] - Loubies-Muñoz, R; Jeldres-Pulgar, A (Ediciones Doyma, S.L., 2021)
Introduction: Trichilemmal cysts correspond to common skin lesions that occur in areas of high density of hair follicles, whose etiology is mainly the trauma of the pilosebaceous unit, constituting the most common cystic lesions of the scalp. Methodology: The objective of the present study was to retrospectively analyze the result of 514 scalp biopsies of lesions clinically corresponding to cysts, these being trichilemmal and/or epidermal, as well as unusual locations specifically characterized for trichilemmal cysts in order to describe gender, age and location of this type of pathology. Results: The results obtained showed consistency with what was reported in the literature regarding the parameters evaluated for trichilemmal cysts, that is, higher prevalence in women, average age of presentation, main location in the scalp and, secondly, facial and cervical. An important result to highlight is that of the total biopsies, 1.8% were reported as a proliferating trichilemmal cyst or with foci of dystrophic calcification, consistent with the literature. Conclusions: Trichilemmal cysts are lesions, in general, asymptomatic and benign, but in a smaller percentage they present their malignant variant corresponding to the proliferating trichilemmal cyst, which often goes unnoticed, even for the pathologist when the lesion is incipient. © 2020